EFFICACY OF DULOXETINE COMPARED WITH IMIPRAMINE IN THE TREATMENT OF MAJOR DEPRESSIVE DISORDER IN INDIAN PATIENTS - ASHOK K DUBEY; OM P RAICHANDANI; SHEETAL P PANDEY (International Journal of Pharma and Bio Sciences, 2012)
Background: Major Depressive Disorder (MDD) is a chronic illness with large contribution to disease burden worldwide. Duloxetine, a dual reuptake inhibitor of 5-HT and NE, is a second generation antidepressant, on which, to the best of our knowledge, there is no study in the Indian adult patients of MDD. There have been studies on duloxetine in MDD patients in other parts of the world, but there has not yet been a study comparing it with the old standard imipramine, a tricyclic acid antidepressant, still commonly used in the primary health care set up. Aims: In this study the efficacy of duloxetine in MDD was compared with that of imipramine. Settings and Design: Prospective observer blinded parallel group comparative study. Materials and Methods: Consenting adult patients (N=60) meeting DSM-IV criteria for MDD who completed six weeks of treatment with, either duloxetine (40 mg) or imipramine (150 mg), were compared for improvement with their base line disease severity, measured by scores on the Hamilton Depression (HAM-D) Rating Scale with 21 items and Clinical Global Impression (CGI) scale. The primary efficacy measure was mean change from baseline to endpoint on the HAM-D scale. Results: The total change in HAM-D score in imipramine group was -25.53 (±7.82) exhibiting an improvement of 67.54% and the total change in HAM-D score in duloxetine group was -20.27(±7.04) showing an improvement of 60.45%. Imipramine showed a slightly greater reduction of HAM-D scores as compared to duloxetine, which was statistically significant, but there was no statistically significant difference between the response rates (80% vs 73.3%) and remission rates (30% vs 26.7%) for imipramine and duloxetine, respectively, at six weeks. Conclusion: The efficacy of duloxetine and imipramine is comparable in MDD with no significant difference in response and remission rates at six weeks.